Game design elements to motivate students / Akma Hidayu Dol@Abdul Wahid and Rafizan Abdul Razak - Dol@Abdul Wahid, Akma Hidayu; Abdul Razak, Rafizan (Universiti Teknologi MARA, Negeri Sembilan, 2022)
To us, it is a big success if we were able to attract the non-accounting students to love the accounting courses. The implementation of Open Distance Learning (ODL) in all public universities in Malaysia has led us to the creation and development of digital games as a tool to attract the non-accounting students to learn accounting in easy and fun ways. The idea was that if the learning was fun, it would encourage students to spend a significant amount of their free time on learning to acquire as much knowledge as they could. In creating a digital game, it is essential to recognise its own purpose in the learning process. Digital games created for education are not the same as for entertainment, which focus on entertaining (Tay et al, 2022). Prior to the development of a game, educators need to know the purpose of the various game features and how the design elements can help achieve the learning objectives. Through analysis of a few articles, we would like to highlight three basic game design element that are used to motivate players and sustain their engagement in learning.